An annotated checklist of the mammals of Paraguay - De La Sancha, Noé U.; López-González, Celia; Dâ€™Elía, Guillermo; Myers, Philip; Valdez, Lourdes; Luisa Ortiz, María (THERYA, 2017)
As the center of convergence of some of the major bioregions of South America, Paraguay is a biodiverse country of biogeographic importance. Yet despite a long history of natural history research, basic knowledge of its fauna, including mammals, is still lacking. The last updated list of Paraguayan mammals was published in 2002, but increased research efforts since that time have brought about numerous changes in the taxonomy and known distribution of many species. We present an updated and annotated checklist on the mammals of Paraguay through 2016. Only species records based on the assessment of some type of verifiable voucher are included here. Because the Paraguay River has been considered a significant biogeographic boundary, the distribution of each species (east of the river, west of the river, present on both sides) is tabulated as well. We recorded 181 native species of mammals, 30 more than in 2002, belonging to 10 orders, 33 families, and 116 genera. Chiroptera (58) was the most diverse order, followed by Rodentia (56), Carnivora (20) and Didelphimorphia (18). Ctenomys pilarensis, C. paraguayensis y C. dorsalis are known only from Paraguay. The inventory is likely incomplete, as well as our knowledge of species distributional limits. Continued collecting of tissues and vouchers, as well as an examination of museum specimens, is necessary to address numerous unsolved questions concerning distribution, taxonomy, ecology, biogeography, population biology and the effects of anthropogenic modification.